Living Qur’an: Pendampingan Pembiasaan Baik dan Pengintegrasian Pembelajaran Aswaja di Madrasah Ibtidaiyah - Damayanti, Ika; Ekantini, Anita; Wijayanti, Inggit Dyaning; Putra, Andhika Yahya; Prasetyo, Alfian Eko Widodo Adi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This service is motivated by the widespread phenomenon that occurs today in the Madrasah Ibtidaiyah (MI) environment with many young people who do not show akhlakul karimah behaviour. This can also be observed by the participation of the younger generation in Islamic organisations that do not reflect Islam according to the guidance of the Qur'an. Islamic schools should be the main platform for basic education in instilling praiseworthy traits and behaviours in students through their learning content or character education programmes. Aswaja-an in learning in MI occupies an important position in providing guidance on faith without overriding nationalism. The objectives of this service are 1) to assist the practice of living Qur'an in schools in the form of habituation of reading Asmaul Husna, and 2) to find out the impact of the implementation of living Quran practices on improving student character. This service uses the PAR type. The service was carried out at MI Ma'arif Sambeng at all grade levels. Living Quran activities are carried out every day before learning activities. The findings of this service are 1) Living Qur'an practices by integrating Aswaja learning as a character education programme at MI Ma'arif Sambeng include: Good habits, extracurricular activities and learning content 2) The impact of the implementation of living Quran practices is to instil students' akhlakul karimah character and increase their love for the country. The implementation of this living qur'an turned out to have an impact felt by MI Ma'arif Sambeng, including the implementation of strengthening character education in the madrasah environment.